Soluble Fibrinogen Triggers Non-cell Autonomous ER Stress-Mediated Microglial-Induced Neurotoxicity - Piers, Thomas M.; East, Emma; Villegas-Llerena, Claudio; Sevastou, Ioanna G.; Matarin, Mar; Hardy, John; Pocock, Jennifer M. (Frontiers in Cellular Neuroscience, 2018)
Aberrant or chronic microglial activation is strongly implicated in neurodegeneration, where prolonged induction of classical inflammatory pathways may lead to a compromised blood-brain barrier (BBB) or vasculature, features of many neurodegenerative disorders and implicated in the observed cognitive decline. BBB disruption or vascular disease may expose the brain parenchyma to ‘foreign’ plasma proteins which subsequently impact on neuronal network integrity through neurotoxicity, synaptic loss and the potentiation of inflammation. Here we show that the blood coagulation factor fibrinogen (FG), implicated in the pathogenesis of dementias such as Alzheimer’s disease (AD), induces an inflammatory microglial phenotype as identified through genetic microarray analysis of a microglial cell line, and cytokine profiling of primary microglia. We also identify a FG-mediated induction of non-cell autonomous ER stress-associated neurotoxicity via an inflammatory pathway that can be blocked by pharmacological inhibition of microglial TNFα transcription or neuronal caspase-12 activity, supporting a disease relevant role for plasma components in neuronal dysfunction.